DECISION SUPPORT SYSTEM FOR TEACHER PERFORMANCE APPRAISAL WITH SIMPLE ADDITIVE WEIGHTING METHOD - Sagala, Jijon Raphita; Hasugian, Penda Sudarto (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Teachers are the most influential component in creating quality educational processes and outcomes. Therefore, improvement efforts are made to improve the quality of education. Schools will not make a significant contribution without the support of professional and qualified teachers. Teachers are really required to have high performance. To improve the quality of teacher performance, the 064022 State Elementary School conducts teacher performance appraisals every 3 months but the mechanism is less effective due to lack of transparency. Research on teacher performance appraisal using the system is applied for efficiency and transparency. The system was developed using the Simple Additive Weighting method. The Simple Additive Weighting method is part of the Decision Support System (DSS) used to help determine decisions based on alternative data and criteria data. Keywords: Decision Support System, Teacher Performance, Simple Addictive Weighting.